Composite ceramic electrostatic chuck and manufacturing method thereof
By printing high-dielectric strength ceramic materials at the electrode gap of the electrostatic suction cup, the problems of breakdown risk and uneven adsorption force at high voltage are solved, and the heat dissipation performance and temperature uniformity of the wafer are improved.
Patent Information
- Application Number
- CN202411460982.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing aluminum oxide/aluminum nitride ceramic electrostatic suction cups have a risk of breakdown at high voltages, resulting in arc accidents, and the design of electrode gaps leads to uneven local adsorption force of the wafer, affecting the heat dissipation performance and temperature uniformity.
High dielectric strength ceramic materials such as tantalum pentoxide or boron hexagonal nitride are printed between electrodes and at the gaps between the electrodes and the outer edges of the electrodes and ceramics, pin holes, and He pores, reducing the gap and increasing the adsorption area between the electrodes and the wafers.
Avoid ceramic breakdown when ensuring high voltage, reduce gaps and improve wafer adsorption, improve heat dissipation performance and temperature uniformity.
Smart Images

Figure CN119419162A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor manufacturing, and relates to an electrostatic chuck for wafer fixing, and in particular to a composite ceramic electrostatic chuck and a manufacturing method thereof. Background Art
[0002] Electrostatic chuck is a key device used to fix wafers in the semiconductor manufacturing process. It uses electrostatic force or other electrical force to adsorb wafers, which is essential to ensure the high quality and consistency of semiconductor products. However, existing aluminum oxide / aluminum nitride ceramic electrostatic chuck products have some technical challenges.
[0003] The dielectric strength of alumina / aluminum nitride ceramic electrostatic chucks is usually around 20kV / mm, which is an important parameter to measure the maximum electric field strength that the material can withstand without breakdown. In order to prevent the applied high voltage from exceeding the dielectric strength of the air, causing the air to be ionized, resulting in unexpected discharge and damage to the equipment, a gap of about 3mm is usually maintained between the electrode and the outer edge of the ceramic. At the same time, in order to ensure that the ceramic will not be broken down and arcing accidents will not occur under the action of high voltage, a gap of about 3mm is also maintained between the electrodes and between them and the edges of the pin hole and the helium hole. Although this gap design can prevent arcing accidents, it also brings some limitations.
[0004] Since the electrode cannot cover the entire ceramic disk surface, the areas where these gaps are located cannot generate adsorption force during use, resulting in uneven adsorption force on the wafer. This uneven adsorption force will affect the heat dissipation performance of these locations on the wafer, and thus have an adverse effect on the uniformity of wafer temperature. In the semiconductor processing process, the uniformity of wafer temperature is crucial to ensure processing accuracy and product quality.
[0005] To improve the heat dissipation and temperature uniformity of the wafer, researchers are actively exploring ways to improve wafer performance by improving the design of the electrostatic chuck. Summary of the invention
[0006] The purpose of the present invention is to print any one of tantalum pentoxide (Ta2O5) and hexagonal boron nitride (BN) with high dielectric strength ceramic materials between electrodes and between electrodes and the outer edge of ceramics, pin holes, and the edge of He pores, so as to reduce the gap while ensuring that the ceramic cast sheet is not broken down at high voltage, make the local adsorption force of the wafer more uniform, and thus improve its heat dissipation performance and temperature uniformity.
[0007] In order to achieve the above object, the present invention provides a method for manufacturing a composite ceramic electrostatic chuck, the method comprising:
[0008] Step 1, providing a ceramic cast sheet, reserving an ejector pin hole and a helium hole, wherein the ejector pin hole is located at the center of the ceramic cast sheet, and the helium holes are evenly distributed on the surface of the ceramic cast sheet, and a metal electrode is printed on the ceramic cast sheet using a screen printing plate to obtain a first cast sheet, wherein the gap between the metal electrode and the ejector pin hole and the helium hole is 0.5 mm-2.5 mm, and the gap between the metal electrode and the outer edge of the ceramic cast sheet is 0.5 mm-2.5 mm;
[0009] Step 2, mixing high dielectric strength ceramic powder, organic solvent, dispersant, binder and plasticizer to prepare high dielectric strength casting slurry, wherein the high dielectric strength ceramic powder includes any one of tantalum pentoxide and hexagonal boron nitride;
[0010] Step 3, replacing the screen printing plate, and printing the high dielectric strength casting slurry at the gap to obtain a second casting sheet;
[0011] Step 4, covering the upper surface of the second cast sheet with a ceramic cast sheet to form a stacked film.
[0012] Optionally, the metal electrode includes a first electrode and a second electrode, wherein the second electrode is arranged outside the first electrode, a first gap exists between the first electrode and the pinhole and the helium hole surrounded by it, a second gap exists between the outer edge of the first electrode and the inner edge of the second electrode, a third gap exists between the second electrode and the helium hole surrounded by it, and a fourth gap exists between the outer edge of the second electrode and the outer edge of the ceramic cast sheet, and the first gap, the second gap, the third gap and the fourth gap are all 0.5mm-2.5mm.
[0013] Optionally, in step 2, the high dielectric strength tape-casting slurry is further doped with a bonding aid, the bonding aid comprises any one of aluminum oxide powder and aluminum nitride powder, and the mass fraction of the bonding aid in the high dielectric strength tape-casting slurry is 0-5%.
[0014] Optionally, in step 2, the mass fraction of the high dielectric strength ceramic powder in the high dielectric strength tape-casting slurry is 25%-50%, the purity of the high dielectric strength ceramic powder is 99%-100%, the particle size is 0.05μm-50μm, and the dielectric strength is greater than 40kV / mm.
[0015] Optionally, in step 2, the organic solvent comprises one or more of anhydrous ethanol, isopropanol, acetone, and toluene, and the mass fraction of the organic solvent in the high dielectric strength casting slurry is 40%-65%.
[0016] Optionally, in step 2, the dispersant includes any one of castor oil phosphate, triethanolamine, and ammonium polyacrylate, and the mass fraction of the dispersant in the high dielectric strength casting slurry is 0.2%-3%.
[0017] Optionally, in step 2, the binder includes any one of polyvinyl butyral and acrylic acid, and the mass fraction of the binder in the high dielectric strength casting slurry is 3%-10%.
[0018] Optionally, in step 2, the plasticizer includes any one of butyl benzyl phthalate, butyl phthalate, and dioctyl phthalate, and the mass fraction of the plasticizer in the high dielectric strength casting slurry is 3%-10%.
[0019] Optionally, after step 4, the method further comprises a debinding and / or sintering step.
[0020] The present invention also provides a composite ceramic electrostatic chuck obtained by the above manufacturing method.
[0021] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:
[0022] The present invention prints any one of tantalum pentoxide and hexagonal boron nitride high dielectric strength ceramic materials between electrodes and between electrodes and ceramic outer edges, pin holes, and He pore edge gaps. Due to its high dielectric strength, the gap can be reduced to 0.5mm-2.5mm while ensuring that the ceramic cast sheet is not broken down at high voltage. At the same time, the adsorption area between the electrode and the wafer can be increased, and the adsorption force on the wafer is improved, thereby effectively improving the heat dissipation performance and temperature uniformity of the wafer. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic cross-sectional view of the alumina cast sheet prepared in the present invention.
[0024] Figure 2 This is a schematic structural diagram of the first cast sheet prepared in the present invention.
[0025] Figure 3 It is a schematic diagram of the structure of the second cast sheet prepared in the present invention; wherein the green area represents the tantalum pentoxide casting slurry.
[0026] Figure 4 It is a schematic cross-sectional view of the composite ceramic body prepared in the present invention.
[0027] Figure ID:
[0028] Pin hole 11
[0029] He pore 12
[0030] First electrode 21
[0031] Second electrode 22
[0032] First gap 31
[0033] Second gap 32
[0034] Third gap 33
[0035] Fourth gap 34
[0036] Alumina cast sheet 41
[0037] The first cast sheet 42
[0038] The second cast sheet 43
[0039] Composite ceramic body 44. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In the description of the present invention, it should be noted that the terms "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0042] The experimental methods used in the following examples were all carried out according to conventional conditions or conditions recommended by the manufacturers unless otherwise specified.
[0043] As described in the background technology, the areas where the electrode gap, pin hole and He pore edge gap are located cannot generate adsorption force when in use, resulting in uneven local adsorption force of the wafer, which will have an adverse effect on the heat dissipation performance and temperature uniformity of the wafer. In order to improve the heat dissipation performance and temperature uniformity of the wafer, the present invention prints any one of tantalum pentoxide and hexagonal boron nitride high dielectric strength ceramic materials at the electrode gap, pin hole and He pore edge gap. Due to its high dielectric strength, the gap can be reduced while ensuring that the ceramic cast sheet is not broken down at high voltage, and at the same time, the adsorption area between the electrode and the wafer can be increased, making the local adsorption force of the wafer more uniform. Specifically, the present invention provides a method for manufacturing a composite ceramic electrostatic chuck, the method comprising:
[0044] Step 1, providing a ceramic cast sheet, reserving a pinhole and a helium hole, wherein the pinhole is located at the center of the ceramic cast sheet, and the helium holes are evenly distributed on the surface of the ceramic cast sheet, and a metal electrode is printed on the ceramic cast sheet using a screen printing plate to obtain a first cast sheet, wherein the gap between the metal electrode and the pinhole and the helium hole is 0.5mm-2.5mm, and the gap between the metal electrode and the outer edge of the ceramic cast sheet is 0.5mm-2.5mm.
[0045] The preparation of the ceramic cast sheet includes the steps of preparing ceramic cast slurry and casting. Ceramic powder, organic solvent, dispersant, binder and plasticizer are mixed to prepare ceramic cast slurry, and the ceramic cast slurry is poured into the slurry feeding trough of the casting machine to cast the ceramic cast sheet and dry it.
[0046] In some embodiments, the ceramic cast sheet includes any one of an alumina cast sheet and an aluminum nitride cast sheet.
[0047] Figure 1 The cross-sectional view of the aluminum oxide cast sheet prepared by the present invention is shown in FIG. The positions of the pin holes 11 and the He gas holes 12 are reserved on the aluminum oxide cast sheet 41 (see FIG. Figure 2 ), the pin hole 11 is used for precise transfer of the wafer, and the He hole 12 is used to introduce helium. Helium has good thermal conductivity and is used for gas flow on the back side of the wafer to help regulate the temperature of the wafer.
[0048] Taking bipolar electrodes as an example, Figure 2As shown, a metal electrode is printed on the alumina cast sheet 41 using a screen printing plate and dried to obtain a first cast sheet 42, wherein the metal electrode comprises a first electrode 21 and a second electrode 22, wherein the second electrode 22 surrounds the first electrode 21, and there is a first gap 31 between the first electrode 21 and the pin holes 11 and the He pores 12 surrounded by it, a second gap 32 between the outer edge of the first electrode 21 and the inner edge of the second electrode 22, a third gap 33 between the second electrode 22 and the He pores 12 surrounded by it, and a fourth gap 34 between the outer edge of the second electrode 22 and the outer edge of the alumina cast sheet 41. The gap can be reduced by using the manufacturing method of the present invention.
[0049] Step 2, mixing high dielectric strength ceramic powder, organic solvent, dispersant, binder and plasticizer to prepare high dielectric strength tape casting slurry.
[0050] The high dielectric strength ceramic powder includes any one of tantalum pentoxide and hexagonal boron nitride. In order to ensure the best effect, the mass fraction of the high dielectric strength ceramic powder in the high dielectric strength tape-casting slurry is 25%-50%, the purity of the high dielectric strength ceramic powder is 99%-100%, the particle size is 0.05μm-50μm, and the dielectric strength is greater than 40kV / mm. In some embodiments, the dielectric strength of the high dielectric strength ceramic powder is 40kV / mm-50kV / mm. Because its dielectric strength is much higher than that of the cast sheet, it can significantly improve the anti-puncture ability of the cast sheet under high voltage.
[0051] In some embodiments, the high dielectric strength casting slurry is further doped with a bonding aid, and the bonding aid includes any one of alumina powder and aluminum nitride powder. Since the bonding aid has high hardness and good wear resistance, it can enhance the bonding force of the cast sheet, but the mass fraction of the bonding aid in the high dielectric strength casting slurry should be less than 5%. If the mass fraction is too high, a current path may be formed under high voltage, resulting in an arc accident. Preferably, an alumina bonding aid can be added to the tantalum pentoxide casting slurry, and an aluminum nitride bonding aid can be added to the hexagonal boron nitride casting slurry to ensure good material compatibility.
[0052] In some embodiments, the organic solvent comprises one or more of anhydrous ethanol, isopropanol, acetone, and toluene, and the mass fraction of the organic solvent in the high dielectric strength tape casting slurry is 40%-65%. The organic solvent can dissolve organic additives such as binders and plasticizers well, and is helpful to form a uniform tape casting slurry.
[0053] In some embodiments, the dispersant includes any one of castor oil phosphate, triethanolamine, and ammonium polyacrylate, and the mass fraction of the dispersant in the high dielectric strength tape casting slurry is 0.2%-3%. The addition of the dispersant can improve the fluidity and stability of the tape casting slurry, so that it exhibits better fluidity and formability during the tape casting molding process.
[0054] In some embodiments, the binder includes any one of polyvinyl butyral and acrylic acid, and the mass fraction of the binder in the high dielectric strength tape casting slurry is 3%-10%. The binder has a bonding effect in the tape casting slurry, can enhance the strength and toughness of the blank, and facilitate subsequent processing operations.
[0055] In some embodiments, the plasticizer includes any one of butyl benzyl phthalate, butyl phthalate, and dioctyl phthalate, and the mass fraction of the plasticizer in the high dielectric strength tape-casting slurry is 3%-10%. The plasticizer acts on the binder to enhance its plasticity, so that the binder softens in a dry or semi-dry state, thereby improving the fluidity and formability of the tape-casting slurry.
[0056] Step 3, replacing the screen printing plate, printing the high dielectric strength casting slurry at the first gap 31, the second gap 32, the third gap 33 and the fourth gap 34 to obtain a second casting sheet 43.
[0057] like Figure 3 As shown, the green area represents tantalum pentoxide tape slurry. As tantalum pentoxide tape slurry has a high dielectric strength, the gap can be reduced from 3mm to 0.5mm-2.5mm while ensuring that the tape is not broken down at high voltage. At the same time, it can increase the adsorption area between the electrode and the wafer, improve the adsorption force on the wafer, and effectively improve the heat dissipation performance and temperature uniformity of the wafer.
[0058] Step 4, covering the upper surface of the second cast sheet 43 with an alumina cast sheet 41, laminating and forming, and opening holes at the reserved positions to obtain pin holes 11 and He pores 12, thereby forming a composite ceramic body 44, Figure 4 The cross-sectional schematic diagram of the composite ceramic body prepared by the present invention is shown in FIG. The composite ceramic body 44 is subjected to debinding and / or sintering to obtain a composite ceramic electrostatic chuck.
[0059] Example 1
[0060] 30% by mass of aluminum oxide powder (purity 98%, particle size 5 μm), 2% by mass of titanium dioxide powder, 55% by mass of anhydrous ethanol, and 1% by mass of castor oil phosphate are put into a ball mill and mixed evenly to obtain a semi-finished ceramic slurry. Then, 6% by mass of polyvinyl butyral and 6% by mass of butyl benzyl phthalate are added to the ceramic slurry, and the mixture is mixed evenly by ball milling to obtain an aluminum oxide tape casting slurry.
[0061] The alumina casting slurry is poured into a slurry feeding tank of a casting machine to cast into an alumina casting sheet and dried.
[0062] Positions for pin holes and He pores are reserved, and a first electrode and a second electrode (bipolar electrode) are printed on the dried alumina cast sheet using a screen printing plate and dried to obtain a first cast sheet, wherein the second electrode is arranged around the outside of the first electrode, and a first gap exists between the first electrode and the pin holes and He pores surrounded by it, a second gap exists between the outer edge of the first electrode and the inner edge of the second electrode, a third gap exists between the second electrode and the He pores surrounded by it, and a fourth gap exists between the outer edge of the second electrode and the outer edge of the alumina cast sheet, and the first gap, the second gap, the third gap and the fourth gap are controlled at 1 mm.
[0063] 30% by mass of tantalum pentoxide powder (purity 99%, particle size 5 μm), 2% by mass of alumina powder, 55% by mass of anhydrous ethanol, and 1% by mass of castor oil phosphate are put into a ball mill and mixed evenly to obtain a semi-finished ceramic slurry. Then, 6% by mass of polyvinyl butyral and 6% by mass of butyl benzyl phthalate are added to the ceramic slurry, and the tantalum pentoxide tape casting slurry is obtained by ball milling and mixing evenly.
[0064] The screen printing plate is replaced, and the tantalum pentoxide casting slurry is printed at the first gap, the second gap, the third gap and the fourth gap and dried to obtain a second casting sheet.
[0065] An alumina cast sheet is covered on the upper surface of the second cast sheet, laminated, and holes are opened at reserved positions to obtain pin holes and He pores, thereby forming a composite ceramic body, and the composite ceramic body is debinded and / or sintered to obtain a composite ceramic electrostatic chuck.
[0066] Example 2
[0067] 35% by mass of aluminum nitride powder (purity 99%, particle size 20 μm), 3% by mass of yttrium oxide powder, 52% by mass of acetone, and 2% by mass of triethanolamine are put into a ball mill and mixed evenly to obtain a semi-finished ceramic slurry. Then, 4% by mass of acrylic acid and 4% by mass of butyl phthalate are added to the ceramic slurry, and the aluminum nitride tape casting slurry is obtained by ball milling and mixing evenly.
[0068] The aluminum nitride casting slurry is poured into a slurry feeding tank of a casting machine to cast an aluminum nitride casting sheet and then dried.
[0069] Positions for pin holes and He pores are reserved, and a metal electrode (monopolar electrode) is printed on the dried aluminum nitride cast sheet using a screen printing plate and dried to obtain a first cast sheet. The gap between the metal electrode and the pin holes and He pores is controlled at 0.5 mm, and the gap between the metal electrode and the outer edge of the aluminum nitride cast sheet is controlled at 0.5 mm.
[0070] 35% by mass of hexagonal boron nitride powder (purity 99%, particle size 20 μm), 3% by mass of aluminum nitride powder, 52% by mass of acetone, and 2% by mass of triethanolamine are put into a ball mill and mixed evenly to obtain a semi-finished ceramic slurry. Then, 4% by mass of acrylic acid and 4% by mass of butyl phthalate are added to the ceramic slurry, and the hexagonal boron nitride tape casting slurry is obtained by ball milling and mixing evenly.
[0071] The screen printing plate is replaced, and the hexagonal boron nitride casting slurry is printed at the gap and dried to obtain a second casting sheet.
[0072] An aluminum nitride cast sheet is covered on the upper surface of the second cast sheet, laminated, and holes are opened at reserved positions to obtain pin holes and He pores, thereby forming a composite ceramic body, and the composite ceramic body is debinded and / or sintered to obtain a composite ceramic electrostatic chuck.
[0073] In summary, the present invention prints any one of tantalum pentoxide and hexagonal boron nitride high dielectric strength ceramic materials between electrodes and between electrodes and the outer edge of ceramics, pin holes, and the edge of He pores. Due to its high dielectric strength, the gap can be reduced to 0.5mm-2.5mm while ensuring that the ceramic cast sheet is not broken down at high voltage. At the same time, it can increase the adsorption area between the electrode and the wafer, and improve the adsorption force on the wafer, thereby effectively improving the heat dissipation performance and temperature uniformity of the wafer.
[0074] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for manufacturing a composite ceramic electrostatic chuck, characterized in that: The method includes: Step 1, providing a ceramic cast sheet, reserving an ejector pin hole and a helium hole, wherein the ejector pin hole is located at the center of the ceramic cast sheet, and the helium holes are evenly distributed on the surface of the ceramic cast sheet, and a metal electrode is printed on the ceramic cast sheet using a screen printing plate to obtain a first cast sheet, wherein the gap between the metal electrode and the ejector pin hole and the helium hole is 0.5 mm-2.5 mm, and the gap between the metal electrode and the outer edge of the ceramic cast sheet is 0.5 mm-2.5 mm; Step 2, mixing high dielectric strength ceramic powder, organic solvent, dispersant, binder and plasticizer to prepare high dielectric strength casting slurry, wherein the high dielectric strength ceramic powder includes any one of tantalum pentoxide and hexagonal boron nitride; Step 3, replacing the screen printing plate, and printing the high dielectric strength casting slurry at the gap to obtain a second casting sheet; Step 4, covering the upper surface of the second cast sheet with a ceramic cast sheet to form a stacked film.
2. The method for manufacturing a composite ceramic electrostatic chuck according to claim 1, characterized in that: The metal electrode includes a first electrode and a second electrode, wherein the second electrode is arranged around the first electrode, there is a first gap between the first electrode and the pinhole and the helium hole surrounded by it, there is a second gap between the outer edge of the first electrode and the inner edge of the second electrode, there is a third gap between the second electrode and the helium hole surrounded by it, there is a fourth gap between the outer edge of the second electrode and the outer edge of the ceramic cast sheet, and the first gap, the second gap, the third gap and the fourth gap are all 0.5mm-2.5mm.
3. The method for manufacturing a composite ceramic electrostatic chuck according to claim 1, wherein: In the step 2, the high dielectric strength tape-casting slurry is further doped with a bonding aid, the bonding aid comprises any one of aluminum oxide powder and aluminum nitride powder, and the mass fraction of the bonding aid in the high dielectric strength tape-casting slurry is 0-5%.
4. The method for manufacturing a composite ceramic electrostatic chuck according to claim 1, wherein: In step 2, the mass fraction of the high dielectric strength ceramic powder in the high dielectric strength tape-casting slurry is 25%-50%, the purity of the high dielectric strength ceramic powder is 99%-100%, the particle size is 0.05μm-50μm, and the dielectric strength is greater than 40kV / mm.
5. The method for manufacturing a composite ceramic electrostatic chuck according to claim 1, wherein: In the step 2, the organic solvent comprises one or more of anhydrous ethanol, isopropanol, acetone, and toluene, and the mass fraction of the organic solvent in the high dielectric strength casting slurry is 40%-65%.
6. The method for manufacturing a composite ceramic electrostatic chuck according to claim 1, wherein: In the step 2, the dispersant includes any one of castor oil phosphate, triethanolamine, and ammonium polyacrylate, and the mass fraction of the dispersant in the high dielectric strength casting slurry is 0.2%-3%.
7. The method for manufacturing a composite ceramic electrostatic chuck according to claim 1, wherein: In the step 2, the binder includes any one of polyvinyl butyral and acrylic acid, and the mass fraction of the binder in the high dielectric strength casting slurry is 3%-10%.
8. The method for manufacturing a composite ceramic electrostatic chuck according to claim 1, wherein: In the step 2, the plasticizer includes any one of butyl benzyl phthalate, butyl phthalate, and dioctyl phthalate, and the mass fraction of the plasticizer in the high dielectric strength casting slurry is 3%-10%.
9. The method for manufacturing a composite ceramic electrostatic chuck according to claim 1, wherein: After step 4, the method further comprises a debinding and / or sintering step.
10. A composite ceramic electrostatic chuck obtained according to the manufacturing method of claims 1-9.
Citation Information
Patent Citations
Electrostatic chuck and electrode sheet for electrostatic chuck
CN101218668A
Electrostatic chuck
JP2002231796A
Porosity-structural material, porosity single crystal high frequency capacitor, and method of manufacturing the same
JP2004172172A
The electrostatic adsorption method of electrostatic chuck and held object
JP2010129673A
Ceramic electrostatic chuck for applications of co-fired by direct bonding and method for manufacturing the same
KR101475860B1